Geodiversity on the Great Sumatran Fault on Sungai Penuh Aspiring for the Geopark Designation, Jambi, Indonesia - Utama, Hari Wiki; Heriberta, Heriberta; Adriadi, Ade; Emilia (UIR PRESS, 2025)
Sungai Penuh is a municipality in Jambi Province which is located in the westernmost part of the administrative region. Naturally, this region has natural beauty as a tourist attraction, where landscape on the Great Sumatran Fault in the Barisan Ranges Zone. The existence of faults plays an important role as the main actor that causes deformation of rocks and natural landscapes, so that it can produce geodiversity. Thus, conditions like this can be used as an important role in the presence of geodiversity for the identification of sustainable geotourism development. The aim of this study is to provide the latest information regarding the existence of the geodiversity in the Great Sumatran Fault for aspiring geopark designation. Research methods for conducting geodiversity features of lithology, stratigraphy, geological structure, and landscape. Then, qualitative assessment of geodiversity includes of education, scientific, and tourism of geodiversity site. Stratigraphically in the research area is composed of pyroclastic Bandan, Sheared Basalt, Sungai Penuh Granodiorite, pyroclastic Pengasih, andesitic lava and volcanic breccia of Mt. Lumut, andesitic lava and volcanic breccia of Mt. Tarasih, andesitic lava and volcanic breccia of Mt. Talang, andesitic lava and volcanic breccia of Mt. Kebongsong, andesitic to basaltic lava and volcanic breccia of Mt. Raya. It has geodiversity that can be used as a geotourism site such as Peak Depati VII Coffee, Dissected Mountains Granitoid Sungai Penuh, Ancient Lake Kerinci, Khayangan Volcanic Plateu, Sungai Penuh Cold Spring, Lake Volcano-tectonic Kerinci. These conditions provide demands for the geotourism loving community to preserve geological heritage in the concept of geological conservation to be proposed as a geological site in the geotourism aspect. So that this role can later have a positive impact on the local community around geotourism objects based on sustainable geotourism development aspiring geopark designation.